mHealth and telemedicine utility in the monitoring of allergic diseases - Kvedarienė, Violeta; Burzdikaitė, Paulina; Česnavičiūtė, Inga (Frontiers in Allergy, 2022)
This literature review discusses the use of mHealth technologies and telemedicine for monitoring various allergic diseases both in everyday life and in the context of COVID-19. Telemedicine, whose popularity, and demand has skyrocketed during the pandemic, rely on mHealth technologies, video calls and websites as a resource-saving and safe way of consulting patients. The incorporation of new mHealth technologies into telemedicine practice may not only be relevant in the context of pandemic restrictions but can also be applied in everyday medical practice as an effective method of patient counseling. The mobile healthcare applications include a wide range of mobile apps for patients' education, monitoring, and disease management. However, applications for the people with food allergies lack relevant information about allergies and, like most other applications, are developed without the contribution of healthcare specialists. During the COVID-19 pandemic, low-risk food-allergic patients were able to rely on telemedicine services where they could get the help, they needed without increasing risk of contracting COVID-19 while saving time. Meanwhile, some applications for allergic rhinitis and asthma patients are showing practical benefits in clinical trials by allowing an efficient assessment of treatment regimens and efficacy. The use of digital symptom diaries further facilitates the implementation of real-life studies. However, for respiratory allergic diseases, the often insufficient quality of pollen prediction needs to be taken into account. Even though studies have shown that asthma is better controlled with mHealth technologies, the quality of mobile apps for asthma patients varies widely, as many products provide information that has not been scientifically proven. Inhaler sensors – have been shown to improve the course of asthma and its monitoring, while push notifications prompting people to take their medication double the likelihood of treatment adherence. Teledermatology has a high level of patient satisfaction – as it is perceived as a more time-saving method of consultation. However, the diagnostic accuracy of contact consultations remains higher. mHealth technologies provide a patient's health data from his/her daily life, which enables insights into behavioral patterns. This closer look at the daily routine can have a significant impact on developing individualized treatment and care guidelines.